CONTRIBUTION OF DISCOVERY LEARNING AND PEER TEACHING ON STUDENT’S MATHEMATICAL CRITICAL THINKING AND SELF CONFIDENT - hendrawanto Hendrawanto (IKIP Siliwangi, 2019)
The purpose of this experiment was to analyze contribution of discovery learning and peer teaching (DL-PT) on student’s mathematical critical thinking (MCT) and self confident (MSC). The experimental took pretest-postest control group design and involved 72 eleventh grade students, a MCT test, a MSC scale, and perception on DL-PT and on DL scales . The study found that on MCT and its N Gain, students getting treatment with DL-PT attained better grade than students taught by DL alone; even if both student’s grades were at medium level, and students realized difficulties on examining the truth of enumeration process and on proving problem. On MSC, there was no different student’s grades between students taught by DL-PT and by DL alone and those grades were at medium level. In addition, there was no association between MCT and SCM, students learned actively during DL-PT and DL and students performed positive opinion on DL-PT and on DL